A Beginner's Guide to Water Management—The ABCs - Lakewatch Florida; Mark Hoyer (EDIS, 2000)
This document is the first in a series of Information Circulars developed by the LAKEWATCH Program. It is an introduction to the basic terminology and concepts used in the water management arena. First published Aug. 2000